2024
DOI: 10.5187/jast.2023.e90
|View full text |Cite
|
Sign up to set email alerts
|

Comparison study between single enzyme and multienzyme complex in distiller’s dred grains with soluble supplemented diet in broiler chicken

Min-Jin Kwak,
Dong-Jin Ha,
Min Young Park
et al.

Abstract: Upregulation of the nutritional value of feed is the major target of various studies in the livestock industry, and dietary enzyme supplementation could aid in digesting the nondegrading nutrients of grains in feed ingredients. Dried distillers’ grains with solubles (DDGS) is a byproduct of the fermentation process in the beverage industry and can be used as a large supply source of fiber in feed. Therefore, we conducted an experiment with male broiler chickens to investigate the effect of various types of enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…As hypothesized, body weights, average daily gain, and daily feed intake increased when birds were fed a higher NSP level diet supplemented with xylanase in the present study. These results are consistent with several previous studies which indicated positive results on growth performance by feeding higher NSP diets supplemented with xylanase [6,16]. The improvement in the broiler's performance is affected by the varying nature and the quantities of NSP present in monogastric diets, and thus careful consideration should be taken to achieve improved performance.…”
Section: Discussionsupporting
confidence: 91%
“…As hypothesized, body weights, average daily gain, and daily feed intake increased when birds were fed a higher NSP level diet supplemented with xylanase in the present study. These results are consistent with several previous studies which indicated positive results on growth performance by feeding higher NSP diets supplemented with xylanase [6,16]. The improvement in the broiler's performance is affected by the varying nature and the quantities of NSP present in monogastric diets, and thus careful consideration should be taken to achieve improved performance.…”
Section: Discussionsupporting
confidence: 91%